Case of eosinophilic granulomatous enterocolitis caused by Strongyloides stercoralis infection with marked hypoalbuminemia and ascites - Ukarapol N. (2014)
We report a 10-year-old boy presenting with generalized pitting edema, ascites, abdominal pain, and chronic mucous diarrhea for 4 weeks. He had underlying diseases of hemoglobin E and juvenile rheumatoid arthritis and had been treated with immunosuppressive agents for a long period of time, including prednisolone and methotrexate. After extensive investigations, Strongyloides stercoralis infection, leading to protein-losing enteropathy and eosinophilic granulomatous enterocolitis, was diagnosed. In the present report, we demonstrate early colonoscopic findings, revealing patchy erythema and small raised mucosal nodules with erosions at the cecum. Histopathological study showed open ulceration with cryptitis, intense infiltration of eosinophils and histiocytes with granuloma formation, in which Strongyloides stercoralis larvae were noted.